Linking care of patients with obesity to outpatient weight control clinics following acute hospitalizations - Harris CM (Dove Medical Press, 2018)
Ché M Harris,1 Lawrence J Cheskin,2 Trina L Gipson-Jones,3 Jennifer A Hartfield,4 Flora Kisuule1 1Division of General Internal Medicine, Johns Hopkins School of Medicine, 2Department of Health, Behavior and Society, The Johns Hopkins Bloomberg School of Public Health, The Johns Hopkins University, Baltimore, MD, USA; 3School of Nursing, Hampton University, Hampton, VA, USA; 4Center for Research on Men’s Health, Vanderbilt University, Nashville, TN, USA Abstract: Despite obesity impacting over one-third of US adults, guideline recommendations have not been effectively utilized by health care providers in hospital settings. Initiation of weight loss plans for obese patients during hospitalizations followed by linkage of care to weight control centers may improve compliance with the guidelines. Provider recognition and awareness that obesity is a chronic condition that warrants inpatient counsel and management with appropriate arrangement of postdischarge follow-up care will be critical to guideline implementation. Keywords: guideline compliance, health systems, intervention, linkage